Clifford's first school day - Bridwell, Norman (New York : Scholastic, 1999)
As a small puppy, Clifford the red dog goes to school with Emily Elizabeth and gets into mischievous trouble during the finger painting, cookie baking, and snack time.
Accelerated Reader
Keywords: Dogs -- Fiction; Schools -- Fiction